Jewish exegesis and Homeric scholarship in Alexandria - Niehoff, Maren (Cambridge, UK ; New York, N.Y. : Cambridge University Press, 2011)
"Systematically reading Jewish exegesis in light of Homeric scholarship, this book argues that more than 2000 years ago Alexandrian Jews developed critical and literary methods of Bible interpretation which are still extremely relevant today. Maren Niehoff provides a detailed analysis of Alexandrian Bible interpretation, from the second century BCE through newly discovered fragments to the exegetical work done by Philo. Niehoff shows that Alexandrian Jews responded in a great variety of ways to the Homeric scholarship developed at the Museum. Some Jewish scholars used the methods of their Greek colleagues to investigate whether their Scripture contained myths shared by other nations, while others insisted that significant differences existed between Judaism and other cultures. This book is vital for any student of ancient Judaism, early Christianity and Hellenistic culture"--
"From the inception of modern research Jewish Bible exegesis in Alexandria has often been regarded as a marginal phenomenon or a puzzling hybrid. It tended to be studied either from the perspective of biblical interpretation in the Land of Israel or as a forerunner of Christian exegesis. Scholars familiar with the Jewish tradition usually focused on the emergence of rabbinic literature, which subsequently became normative. If Alexandrian exegesis was at all taken into account, it was characteristically either construed as a derivative phenomenon depending on its counterpart in Jerusalem or dismissed as an alien body of literature, which reflects Greek ideas and anticipates Christianity while failing to resonate in traditional Jewish circles"--
Includes bibliographical references (p. 188-207) and indexes.
Description based on print version record.
Keywords: LITERARY COLLECTIONS / Ancient, Classical & Medieval; Bible. -- Criticism, interpretation, etc., Jewish; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D.; Jewish learning and scholarship -- Egypt -- Alexandria -- History -- To 1500.; Jews -- Civilization -- Greek influences; Hellenism; Alexandria (Egypt) -- Religion; RELIGION / Biblical Criticism & Interpretation / Old Testament; Electronic books